RESEARCH ON MICROSTRUCTURE AND REDISTRIBUTION OF THE MOISTURE CONNECTION FORMS IN THE MODEL SYSTEMS OF CONFECTIONERY SEMI-FINISHED PRODUCT WITH BANANA POWDER - Mariia IANCHYK (Stefan cel Mare University of Suceava, 2017)
The article is devoted to research of model systems of a new finishing confectionery semifinished product which contains sugar fondant, plant powder, butter and surfactant - citric acid ester. A derivatographic analysis of the model systems of a confectionery semi-finished product was carried out and the distribution of moisture connection forms was investigated. Types of moisture connections were determined in terms of the classification system of Rehbinder P.A. which is based on a magnitude of connection energy of water with material. The results of microstructure researches of model systems are presented in the article. It has been found that particles of banana powder do not act as crystallization centers and therefore do not exert impact on the process of grain formation of sucrose in fondant mass. The expediency of surfactant use in the production of a new confectionery semi-finished product with banana powder is proved.